The role of Indonesian national soldiers in the Covid-19 outbreak - Okta Andrian Fitriansyah; Ansori Zaini; Edi Suhardono; Rudi Sutanto (Technium Social Sciences Journal, 2021)
Modern warfare is not just muscular warriors or laser-blended weapons, but the level of intelligence and morality. The war is now a strategy to utilize space (media) and time (moments or events), in winning the hearts of the public. The Covid-19 outbreak, is a serious threat to Indonesia in terms of defense and security. The government must be able to prepare as well as possible to anticipate the various possibilities and potential national threats. The military is the best organization in every country, because the military will always be ready to face all threats that can interfere with the sovereignty of the country, so it is interesting for the writer to make a description of the role of the TNI in dealing with Covid-19 with the Barry Buzan threat assessment framework. The study was conducted with a descriptive approach to phenomenological qualitative trying to understand the meaning of various events and human interactions in a particular situation. Hope the author, with this paper can provide benefits for the benefit of the nation and state.